Turba Ihsanniat Parent in Central Java to Strengthen Islamic Boarding School Alumni Networks - Ahmad Insya' Ansori; Moh. Ulumuddin; Bustanul Arifin (LP3M STAI At-Tahdzib Jombang, 2026)
This community service program stems from the need to strengthen the alumni network of Islamic boarding schools, consolidate regional consulates, and increase the participation of students' guardians in supporting the sustainability of Islamic boarding school education. The Turba Ihsanniat Induk Team 1 activity was carried out at six consulates in Central Java, namely Sukoharjo, Sragen, Grobogan, Demak, Kudus, and Pati on May 31 to June 2, 2026 with a total of 118 participants recorded. The purpose of the service is to strengthen alumni ties, socialize the Ihsanniat Induk program, strengthen the consulate structure, recruit prospective new students, and absorb community aspirations. The method used is participatory mentoring through initial coordination, face-to-face forums, introductions, program socialization, alumni dialogue, aspiration mapping, and institutional follow-up. The results of the activity showed the emergence of a positive community response, strengthening the routine alumni agenda, development alms initiatives, the formation of the Pati consulate structure, mapping the needs of teaching staff, and recommendations for improving Islamic boarding school governance. This activity resulted in initial transformations in the form of strengthened alumni communication, renewed collective awareness of the consulate's role, and the development of a follow-up agenda based on local needs. This community service program confirmed that alumni outreach can be an effective strategy for empowering Islamic boarding school communities if managed as a space for dialogue, organizing, and activating social capital.